Al-Iqtishad : Jurnal Ilmu Ekonomi Syariah ( Journal of Islamic Economics) - Abdulla Hamzah Al-Hadrami (Fakultas Syariah dan Hukum UIN Syahida Jakarta, 2017)
The Important Selection Criteria In Choosing Islamic Banks: A Survey In Bahrain Abdulla Hamzah Al-Hadrami1 , Sutan Emir Hidayat2 , Mohamed Isa Al-Sharbiti3 165-184 Islamic Banking Existence And Domestic Credit: Study At Seven Countries Hamdan Yuafi1 , Anton Bawono2 185-202 Risk Of Debt-Based Financing In Indonesian Islamic Banking Kharisya Ayu Effendi 203-212 Determining Factors Of Deposit Level Of Islamic Bank In Indonesia Sofyan Baehaqie1 , Idqan Fahmi2 , Irfan Syauqi Beik3 213-226 Comparing Efficiency And Productivity In Islamic Banking: Case Study In Indonesia, Malaysia And Pakistan Ahmad Rodoni1 , M. Arskal Salim2 , Euis Amalia3 , Rezki Syahri Rakhmadi 227-242 Zakah For Asnaf Al-Gharimun In Brunei Darussalam: Concepts And Practices Rose Abdullah1 , Abdurrahman Raden Aji Haqqi2 243-258 Effective Zakah Distribution: Highlighting Few Issues And Gaps In Kedah, Malaysia M Ashraf Al Haq1 , Norazlina Binti Abd. Wahab2 259-288 Currency System And It’s Impact On Economic Stability Desmadi Saharuddin1 , Ali Rama2 289-310 Bankruptcy Model Analysis: Comparative Studies Between Sharia And Non Sharia Manufacturing Companies Ruhadi1 , Muhamad Umar Mai2 311-330 Fatwa And The Development Of Sharia Financial Industry: A Lesson From Indonesia Ma’ruf Amin 3341-350